Instrumentos musicais com ênfase no violão - Ottes, Elaine Coron; Almeida, Gisele Rodrigues; Gonçalves, Jesuína Aparecida; Bordinhão, Andréa Chiozini; Carraro, Márcia Regina Simpione (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
VER PDF